Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Peningkatkan Semangat Belajar Siswa dan Implikasinya Terhadap Hasil Belajar Siswa - Solihatul Fadila; Euis Eka Pramiarsih; Ria Herdhiana (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
The purpose of this study entitled The Effect of Cooperative Learning Type Snowball Type Throws Against Increasing Student Learning Spirit and Its Implications in Learning Outcomes, written by Solihatul Fadila, with Euis Eka Ei Pramiarsih and Ria Herdhiana's supervisors.The purpose of this study was to examine the use of snowball throwing learning models on business communication subjects on the enthusiasm and learning outcomes of students. The population of this study is SMK Negeri 3 Bandung. To achieve the purpose of this study, sampling was determined by Sampling Purposive method so that 34 samples were selected from the experimental class and kontrol class. The research instrument used was observation, tests, questionnaires and documentation. Observations on the use of snowball throwing learning models are very good. he results of the tests were normality test, homogeneity test, t test, gain test and correlation test. The results of the study show that the snowball throwing model can improve the enthusiasm and learning outcomes of students, and all indicators of enthusiasm and learning outcomes are achieved. The advantages of this model are very useful and as an alternative to learning that wants good enthusiasm and learning outcomes.